Synthesis and Characterization of some new heterocyclic derivatives from aromatic carbonyl ‎compounds and carboxylic acids with Evaluation some of them for biological activity - Al-Khazraji, Shaima Ibraheem; Ahamed, Luma S.; Ali, Rana Abid (Iraqi Journal of Science, 2024)
In this research investigation, a total of eighteen diverse tetra- and penta-lateral cyclic compounds were synthesized. These included 1,3,4-thiadiazole, thiazolidin-4-one (via an alternative method), 1,2,4-triazole, carbothioamide, thiazole-4-one, azetidin-2-one, and oxazole. The synthesis procedure entailed a sequence of reactions. The thiazolidine-4-one 1 was obtained by reaction p-aminobenzoic acid with thiosemicarbazide, followed by treatment with p-tolualdehyde to produce Schiff base 2. Reaction Schiff base 2 with mercaptoacetic acid in dry benzene was carried out to produce thiazolidine-4-one 3. In another synthesis pathway, the esterification of p-nitro benzoic acid with ethanol in the presence of sulfuric acid was obtained to formation of compound 4. Compound 4 was subsequently reacted with thiosemicarbazide, yielding compound 5. Cyclization of compound 5 was then achieved using 4% sodium hydroxide solution. This formed the 1,2,4-triazole heterocycle, designated compound 6. Thiosemicarbazone 7-9 were prepared by reaction of thiosemicarbazide with different aldehydes. Additionally, 2-substituted-1,3-thiazolidine-4-one derivatives 10-12 were synthesized through the reaction of thiosemicarbazone with chloroacetic acid in the presence of anhydrous sodium acetate. The Oxazole derivative 15 was obtained through a series of reactions starting with the reaction of p-amino benzoic acid with ethyl chloroacetate, resulting in compound 13. Compound 13 was then treated with urea to obtain compound 14, followed by a reaction with 4-phenyl phenacyl bromide to yield the final product, the Oxazole derivative 15. The 2-aminooxadiazole derivative 16 was synthesized by reaction urea with 4-bromoacetophenone which was reacted with 4-bromobenzaldehyde to produce Schiff base derivative 17. Finally, β-lactam 18 is obtained through reaction Schiff base with chloroacetyl chloride in the presence of triethyl amine. FT-IR, 1H-NMR, and 13C-NMR spectroscopy were used to confirm their proposed structures. Moreover, the antibacterial and antifungal activities of certain synthesized compounds, specifically 2,3,6,11,13,15,17, and 18, were assessed against Staphylococcus aureus, Escherichia coli, and Candida albicans, demonstrating encouraging outcomes.Keywords: Antibacterial, antifungal activity, oxadaizole, heterocyclic derivatives, Oxazole.